IMPLEMENTASI UNDANG UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA TERHADAP HAK HAK PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA (PPPK) DI LINGKUNGAN FAKULTAS HUKUM UNIVERSITAS MULAWARMAN SAMARINDA - Ahmad Yani (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT  “THE IMPLEMENTATION OF  LAW NUMBER 5 YEAR 2014 CONCERNING STATE INSTRUMENT FOR CIVIL RIGHTS OF GOVERMENT EMPLOYEE WITH WORK AGREEMENT IN THE FACULTY OF LAW UNIVERSITY MULAWARMAN SAMARINDA”. At the year of 2014 mark the end of the reign of Susilo Bambang Yudhoyono giving us a bureaucracy reform through the law number 5 year 2014.this , the writer try to research to know how much the implementation of the law number 5 year 2014 about the right of non government employee or a government employee with work agreement. Data Analysis method that used in this writing is Juridical-empiric. The Writer uses a written law or non written law as a material to process data that will be taken by observation and interview on mulawarman university faculty of law. Keyword : Law number 5 year 2014,Government employee with work agreement